EFFECT OF FLASK VIBRATION ON GRAY CAST IRON CHARACTERISTICS PREPARED BY LOST FOAM CASTING - Sutiyoko, Sutiyoko; Lutiyatmi, Lutiyatmi; Suyitno, Suyitno; Soekrisno, R. (Jurnal Rekayasa Mesin, 2025)
Parameter selection in lost foam casting can reduce the casting defect. Flask vibration is a critical parameter that significantly influences the casting quality in the lost foam casting. This research aims to investigate the effect of the flask vibration duration on fluidity, porosity, and surface roughness of gray cast iron in the lost foam casting. The unbounded silica sand was placed in the flask for the vibration process. An expanded polystyrene foam pattern which is cross-shaped and has four thicknesses was embedded in unbounded silica sand. The flask was vibrated by a vibrator machine for 2–10 minutes to compact the molding sand in amplitude and frequency of 1 mm and 23 Hz. Fluidity was measured based on the length of the casting for each thickness, while porosity was measured using the Archimedean principle to obtain the actual density. The fluidity and the porosity of the gray cast iron increase with the flask vibration duration. On the other hand, increasing the flask vibration duration decreases the surface roughness of this material.